An Akan Christian Appraisal of Ancestor Christology - Isaac Boaheng (Social Sciences, Humanities and Education Journal (SHE Journal), 2023)
The contextualization of the Christian faith is indispensable to the planting, development and survival of the Christian religion in any given environment. In the African context, attempts to contextualize Christianity have led to the formulation of African Functional Christologies aimed at making Christianity more meaningful to the African audience. One of such Christologies is Ancestor Christology which designates Christ as Ancestor, superior to all African ancestors. Though very appealing to the African audience, Ancestor Christology has serious pitfalls which challenge its legitimacy as an authentic Christian Christological model. Different scholars have critiqued Ancestor Christology from different African cultural perspectives and have expressed concerns about its overall contribution to the orthodoxy of African Christian theology. Renewed interest in the subject in recent times has prompted this paper which appraises the ancestor-Christological model from an Akan Christian perspective. The paper is a literature-based research that gathered data from such scholarly sources as books, journal articles, and dissertation/theses. After analyzing the Akan concept of ancestorship, the paper then surveys the works of selected Ancestor Christologians to give an overview of the doctrine in question. Ancestor Christology is, then, evaluated through an Akan Christian lens, noting its strengths and weaknesses. The paper found that even though Ancestor Christology may facilitate the African Christian understanding of Christ’s care for the existential needs of the Akan/African, it has the tendency of encouraging ancestor worship, reducing Christ to a human being with no divine nature, and negating the resurrection, thereby nullifying the key foundations of the Christian faith. Yet, this does not necessarily mean the concept of Ancestor Christology should be rejected outright. African scholars may brainstorm to know how best this Christological model may be improved. The paper recommended, among others, that ontological and functional Christologies must always be treated together rather than in isolation